Pojokbelia : The Study of Smart Phone Application Development as Communicative, Informative and Educative (KIE) Media Innovation for Adolescent Reproductive Health - Kusumawardani, Lita Heni; Jauhar, Muhamad; Rasdiyanah, Rasdiyanah; Desy Rohana, I Gusti Ayu Putu (Jurnal Keperawatan Soedirman, 2018)
Introduction: The increase of adolescent population globally and nationally makes adolescent as vulnerable group to health problems, especially reproductive health. Adolescent has curiosities, like challenges, and dare to take risks. The impact is unwanted pregnancy, sexual transmition diseases, and abortion. Therefore, there is a need of KIE media for adolescent reproductive health based on information technology: smart phone applications.Objective: To identify research articles on smart phone use as KIE media for adolescent reproductive health.Method: Literature study in 20 journals through Google Scholar, Proquest, and EBSCO in the last 5 years, keywords adolescent reproductive health, health education, smartphone application. Data are analyzed in tables contain title, author, year, methodology, result, and recommendation.Result: Smartphone application as KIE media for adolescent reproductive health effectively increased the connection of adolescents with parents and health workers, improved sexual transmition diseases screening, was more attractive and innovative, took into privacy, was accurate information, wider reach, easy access, affordable costs, interactive, practical, and appropriate to the needs of today's adolescent.Conclusion: Smartphone applications such as text message, social media, and website can open adolescent access to get fast and accurate health information. The media development needs to focus on the characteristics and needs of adolescent and can be integrated with adolescent health programs.